Towards a "colouring of races". The materials of polychromy in sculptural depictions of black bodies at the end of the 19th century - (:unkn) unknown (My University, 2023)
Particular attention was paid to the accuracy of physical features in sculpted representations of Africans during the second half of the 19th century. At the time, representations of Africans were mostly sculpted in coloured materials used to imitate the natural colours of the subject depicted. Since skin colour was an important racial marker, sculptors sought to make it visible through a “coloration of the races”, as the sculptor Jean-Baptiste Carpeaux (1827-1875) wrote. Thus, the choice of colour does not appear to be a picturesque or fanciful addition, but rather an element with a carefully thought out meaning. This article presents the initial results of my research focusing on the use of polychrome materials in sculpted representations of black bodies at the end of the 19th century. This paper focuses on the nature of the materials and colours used to convey the colour black, whether decided by the sculptor or repainted at a later date. This consideration of the different colours of materials and pigments will lead to a study of the symbolic value of skin tone.
Keywords: African Research